Cracking the perfusion code?: Laser-assisted Indocyanine Green angiography and combined laser Doppler spectrophotometry for intraoperative evaluation of tissue perfusion in autologous breast reconstruction with DIEP or ms-TRAM flaps - Ludolph, Ingo; Arkudas, Andreas; Schmitz, Marweh; Boos, Anja; Taeger, Christian; Rother, Ulrich; Horch, Raymund E.; Beier, Justus (Journal of Plastic Reconstructive and Aesthetic Surgery, 2016)
The aim of this prospective study was to assess the correlation of flap perfusion analysis based on laser-assisted Indocyanine Green (ICG) angiography with combined laser Doppler spectrophotometry in autologous breast reconstruction using free DIEP/ms-TRAM flaps. Between February 2014 and July 2015, 35 free DIEP/ms-TRAM flaps were included in this study. Besides the clinical evaluation of flaps, intraoperative perfusion dynamics were assessed by means of laser-assisted ICG angiography and post-capillary oxygen saturation and relative haemoglobin content (rHb) using combined laser Doppler spectrophotometry. Correlation of the aforementioned parameters was analysed, as well as the impact on flap design and postoperative complications. Flap survival rate was 100%. There were no partial flap losses. In three cases, flap design was based on the angiography, contrary to clinical evaluation and spectrophotometry. The final decision on the inclusion of flap areas was based on the angiographic perfusion pattern. Angiography and spectrophotometry showed a correlation in most of the cases regarding tissue perfusion, post-capillary oxygen saturation and relative haemoglobin content. Laser-assisted ICG angiography is a useful tool for intraoperative evaluation of flap perfusion in autologous breast reconstruction with DIEP/ms-TRAM flaps, especially in decision making in cases where flap perfusion is not clearly assessable by clinical signs and exact determination of well-perfused flap margins is difficult to obtain. It provides an objective real-time analysis of flap perfusion, with high sensitivity for the detection of poorly perfused flap areas. Concerning the topographical mapping of well-perfused flap areas, laser-assisted angiography is superior to combined laser Doppler spectrophotometry.
EVALuna2:15280